Review article: Burnout in emergency medicine physicians. (9th October 2013) - Arora, Manit; Asha, Stephen; Chinnappa, Jason; Diwan, Ashish D
Abstract Training and the practice of emergency medicine are stressful endeavours, placing emergency medicine physicians at risk of burnout. Burnout syndrome is associated with negative outcomes for patients, institutions and the physician. The aim of this review is to summarise the available literature on burnout among emergency medicine physicians and provide recommendations for future work in this field. A search of MEDLINE (1946–present) (search terms: 'Burnout, Professional' AND 'Emergency Medicine' AND 'Physicians'; 'Stress, Psychological' AND 'Emergency Medicine' AND 'Physicians') and EMBASE (1988–present) (search terms: 'Burnout' AND 'Emergency Medicine' AND 'Physicians'; 'Mental Stress' AND 'Emergency Medicine' AND 'Physicians') was performed. The authors focused on articles that assessed burnout among emergency medicine physicians. Most studies used the Maslach Burnout Inventory to quantify burnout, allowing for cross‐study (and cross‐country) comparisons. Emergency medicine has burnout levels in excess of 60% compared with physicians in general (38%). Despite this, most emergency medicine physicians (>60%) are satisfied with their jobs. Both work‐related (hours of work, years of practice, professional development activities, non‐clinical duties etc.) and non‐work‐related factors (age, sex, lifestyle factors etc.) are associated with burnout. Despite the heavy burnout rates among emergency medicine physicians, little work has been performed in this field. Factors responsible for burnout among various emergency medicine populations should be determined, and appropriate interventions designed to reduce burnout.